The violin compositions of Risto Savin in the perspective of violinistic creativity in the Slovenian lands at the beginning of the twentieth century - Zupančič, Maruša (De musica disserenda, 2022)
This paper is a presentation of violin compositions by Risto Savin in the context of violin creativity at the beginning of the twentieth century. Although the first violin compositions in the Slovenian provinces had been written as early as the seventeenth century, the Sonate pour le piano-forte avec accompagnement de violon of Matej Babnik is today regarded as the first Slovenian violin composition. It was published around 1817–1820 in Vienna. By the end of the nineteenth century, a few violin compositions had been written by Slovenian composers (Gojmir Krek, Josip Ipavec and Benjamin Ipavec). However, their works were more suited to amateur performance in music salons. In the early twentieth century things changed, especially in the field of violin creativity, as well as in violin performance. The first eminent Slovenian violin composer was Risto Savin. He wrote six pieces for violin and piano, which were suitable as they stood for concert use.